2020
DOI: 10.3390/medicina56060299
|View full text |Cite
|
Sign up to set email alerts
|

Lactation Ketoacidosis: A Systematic Review of Case Reports

Abstract: Background and Objective: Lactation ketoacidosis is a rare cause of high anion gap metabolic acidosis affecting breastfeeding mothers. We aim to review and analyze all cases of lactation ketoacidosis reported. Materials and Methods: A systematic search of PubMed/MEDLINE and Cumulative Index to Nursing and Allied Health Literature (CINAHL), identifying relevant case reports published from 1 January 1970 to 31 December 2019. We extracted the following data: the first author, country, year of publication, age of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Ketoacidosis has been reported to be induced by a low carbohydrate diet [5]. A negative energy balance due to any stressor exacerbates ketogenesis; thus, a stressor such as breastfeeding can produce lactation ketoacidosis [6].…”
Section: Discussionmentioning
confidence: 99%
“…Ketoacidosis has been reported to be induced by a low carbohydrate diet [5]. A negative energy balance due to any stressor exacerbates ketogenesis; thus, a stressor such as breastfeeding can produce lactation ketoacidosis [6].…”
Section: Discussionmentioning
confidence: 99%
“…In the veterinary literature this has been well described as “bovine ketosis.” 3 The literature on this condition in humans is limited mainly to case reports, the first of which was published in 1982. 4 A recent systematic review by Al Alawi identified only 18 published cases globally over the last 30 years 2 . We report a case of severe LKA that was identified in a young postpartum patient who presented with common chief complaints.…”
Section: Introductionmentioning
confidence: 90%
“…4 A recent systematic review by Al Alawi identified only 18 published cases globally over the last 30 years. 2 We report a case of severe LKA that was identified in a young postpartum patient who presented with common chief complaints. A venous blood gas revealed a pH of 7.0, pCO2 of 19 consistent with metabolic acidosis with appropriate respiratory compensation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations